Innovative Design, Analysis and Development Practices in Aerospace and Automotive Engineering I-DAD 2014, February 22 - 24, 2014 - Bajpai, Ram P; Chandrasekhar, U; Arankalle, Avinash R (Lecture Notes in Mechanical Engineering,, 2014)
The book presents the best articles presented by researchers, academicians and industrial experts in the International Conference on â_oInnovative Design, Analysis and Development Practices in Aerospace and Automotive Engineeringâ__. The book discusses new concept designs, analysis and manufacturing technologies, where more swing is for improved performance through specific and/or multifunctional linguistic design aspects to downsize the system, improve weight to strength ratio, fuel efficiency, better operational capability at room and elevated temperatures, reduced wear and tear, NVH aspects while balancing the challenges of beyond Euro IV/Barat Stage IV emission norms, Greenhouse effects and recyclable materials. The innovative methods discussed in the book will serve as a reference material for educational and research organizations, as well as industry, to take up challenging projects of mutual interest.